Strategic appraisal of interdependent infrastructure provision - Young, K (2015)
Infrastructure services are of fundamental importance to a country's economic and social well-being; however, decisions about such investments are complex, involving multiple actors, high levels of uncertainty and creating a multi-decadal lock-in to the choices made. Methodologies to assist with such decisions ('appraisal' methodologies) have developed to consider many of these complexities, yet they remain sector specific, ignoring interdependencies between infrastructure networks. Such methodologies thereby ignore the opportunities or vulnerabilities derived from these inter-relationships, simply assuming that cross-sectoral services will be provided, and ignoring the constraints created for future development. Furthermore, the siloed methodologies make calculation of the total system effects impossible, undermining strategic plans and obscuring any need (or ability to) prioritise across sectors. The work herein aimed to develop and demonstrate a strategic approach, capable of providing a more complete valuation of infrastructure investments by taking the interdependencies between the networks into account. In so doing, it examined the hypothesis that use of such a methodology could help deliver more robust outcomes. The work is founded on development of a common, cross-sector appraisal methodology: fifteen common, monetised infrastructure performance metrics, developed by reviewing the strategic priorities of infrastructure and the existing sectoral cost benefit analyses. This was integrated with best practice from portfolio, pathway and real option approaches to create a longer term, system focused analysis of the decision space. Testing the framework through a case study (the Thames Hub Vision), chosen specifically for its high number of sectors, diversity of impacts and magnitude of its interdependencies, it examines the information gained by the increased methodological complexity. The results demonstrate that current appraisal methods are indeed incomplete, with interdependencies creating additional value and the opportunity for increased robustness. Indeed, ignored system effects are found to be sufficient to reverse the result of the analysis and future effects enabled by the investments are found to be up to an order of magnitude greater than the direct impacts recorded by current appraisals. Furthermore, the response and sensitivity to uncertainty is shown to be affected by consideration of the system effects, both directly, through their application to multiple assets and indirectly, through interaction with the wider investment landscape. The proposed approach captures these values and relationships, allowing more informed decisions to be made. In addition, a decision support tool is developed providing the means to identify which opportunities stakeholders wish to maintain, how these can be created and which variables must be tracked to ensure the opportunities remain valid. The work therefore promotes a more active, strategic approach to infrastructure investment, allowing translation between national targets, regional stakeholder values and sector-specific technical requirements, to create a more holistic plan for a country’s infrastructure networks.